2019
DOI: 10.1002/jcp.28634
|View full text |Cite
|
Sign up to set email alerts
|

Competing endogenous RNA network and prognostic nomograms for hepatocellular carcinoma patients who underwent R0 resection

Abstract: The prognosis of hepatocellular carcinoma (HCC) after R0 resection is unsatisfactory due to the high rate of recurrence. In this study, we investigated the recurrence-related RNAs and the underlying mechanism. The long noncoding RNA (lncRNA), microRNA (miRNA), and messenger RNA (mRNA) expression data and clinical information of 247 patients who underwent R0 resection patients with HCC were obtained from The Cancer Genome Atlas. Comparing the 1-year recurrence group (n = 56) with the nonrecurrence group (n = 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…As shown in Tables 4 and 5, in current predictive models or scoring systems of HCC recurrence after hepatectomy, MVI is simply classified as present or absent. 13,16,17,19,[21][22][23][24][25][26][27][28]30,32,34 Some studies do not even evaluate MVI. 12,14,15,18,29,31,33,36,39 Considering the potential role of MVI in predicting the recurrence of HCC in patients following hepatectomy, MVI absence (M0) was used as a reference indicator in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Tables 4 and 5, in current predictive models or scoring systems of HCC recurrence after hepatectomy, MVI is simply classified as present or absent. 13,16,17,19,[21][22][23][24][25][26][27][28]30,32,34 Some studies do not even evaluate MVI. 12,14,15,18,29,31,33,36,39 Considering the potential role of MVI in predicting the recurrence of HCC in patients following hepatectomy, MVI absence (M0) was used as a reference indicator in our study.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,20,29,35,36 In some cases, predictive analyses are performed using an indicator of disease-free survival (DFS). 12,14,[16][17][18][19][21][22][23][24][25][26][27][31][32][33][34] Some investigators have suggested using the time to recurrence, rather than recurrence-free survival, as the endpoint to predict and evaluate ER after HCC resection. 41 Second, these systems tend to only be used for specific populations, limiting interpretation or the detection of consistent patterns across groups.…”
Section: Introductionmentioning
confidence: 99%
“…ceRNA networks modify or control the expression of key genes in many diseases. For instance, ceRNA network analysis has been mostly used in cancer research [ 49 ]. With ceRNA studies extending to autoimmune diseases, many important molecules and key signalling networks have been unveiled, such as the Jak-STAT signalling pathway [ 17 ], complement and coagulation cascades [ 50 ], and apoptosis[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the prevalence of HCC is gradually increasing, especially in non-traditional high incidence areas, such as the United States and Europe. Most HCC patients are likely to be diagnosed at an advanced stage since HCC is asymptomatic at early stages, and effective biomarkers for early diagnosis and prognostic prediction are lacking ( Lei et al, 2019 ; Li et al, 2019b ; Liu et al, 2019 ). Currently, the main treatments for HCC include radiofrequency ablation, surgical resection, immunotherapy, and liver implantation, among others.…”
Section: Discussionmentioning
confidence: 99%